2022
DOI: 10.3390/cells11050874
|View full text |Cite
|
Sign up to set email alerts
|

Tph2 Gene Expression Defines Ethanol Drinking Behavior in Mice

Abstract: Indirect evidence supports a link between disrupted serotonin (5-hydroxytryptamine; 5-HT) signaling in the brain and addictive behaviors. However, the effects of hyposerotonergia on ethanol drinking behavior are contradictory. In this study, mice deficient in tryptophan hydroxylase 2 (Tph2−/−), the rate-limiting enzyme of 5-HT synthesis in the brain, were used to assess the role of central 5-HT in alcohol drinking behavior. Life-long 5-HT depletion in these mice led to an increased ethanol consumption in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Serotonin was associated with ethanol consumption and addiction [94]. Genetic deficiency of TPH2 in mice promotes increased ethanol consumption associated with an ethanol antidepressant phenotype (shorter immobility time in the forced swim test) [95]. Low tryptophan availability has been linked to alcohol dependence [94].…”
Section: Genetics Epigenetics and Tryptophan Metabolismmentioning
confidence: 99%
“…Serotonin was associated with ethanol consumption and addiction [94]. Genetic deficiency of TPH2 in mice promotes increased ethanol consumption associated with an ethanol antidepressant phenotype (shorter immobility time in the forced swim test) [95]. Low tryptophan availability has been linked to alcohol dependence [94].…”
Section: Genetics Epigenetics and Tryptophan Metabolismmentioning
confidence: 99%
“…5-HT has been also found to control segmental motor patterns in small intestine. A study performed in tryptophan hydroxylase deficient (Tph2-/- mice) mice demonstrated the functional aspects of 5-HT in GI motility mainly by attributing with significant reductions in contractile complexes and synaptic transmission due to lower level of 5-HT[ 108 , 109 ]. This is further indicative for the significance of serotonergic neurons, comparing to EC cells for constitutive GI motility.…”
Section: Intestinal Microbiome and Serotonergic Signallingmentioning
confidence: 99%